Toric Fano three-folds with terminal singularities - Kasprzyk, Alexander M. (Tohoku University, Mathematical Institute, 2006)
This paper classifies all toric Fano 3-folds with terminal singularities. This is achieved by solving the equivalent combinatoric problem; that of finding, up to the action of GL(3,Z), all convex polytopes in Z^3 which contain the origin as the only non-vertex lattice point.